2020
DOI: 10.1016/j.jclepro.2019.119298
|View full text |Cite
|
Sign up to set email alerts
|

More sustainable European diets based on self-selection do not require exclusion of entire categories of food

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 54 publications
(79 reference statements)
7
27
0
1
Order By: Relevance
“…Thus, while nutritionally healthy diet and environment preservation are overall in alignment, these dimensions however may not always go hand in hand. This observation seems in line with previous works showing that unhealthy foods, such as sweet and fat food, may exhibit low environmental impacts (Clark et al, 2019;Perignon et al, 2017) and observational studies showing that the lowest emitting diets are not systematically the most sustainable as regards their nutritional values (Vieux et al, 2020). This is of great importance from a public health point of view as it highlights the need of fostering both environment-friendly and healthy diets.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, while nutritionally healthy diet and environment preservation are overall in alignment, these dimensions however may not always go hand in hand. This observation seems in line with previous works showing that unhealthy foods, such as sweet and fat food, may exhibit low environmental impacts (Clark et al, 2019;Perignon et al, 2017) and observational studies showing that the lowest emitting diets are not systematically the most sustainable as regards their nutritional values (Vieux et al, 2020). This is of great importance from a public health point of view as it highlights the need of fostering both environment-friendly and healthy diets.…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation of simulations or models is that they remain theoretical. Indeed, the relationship between the health and environmental impacts of self-selected diets is more complex than that between single foods/food groups [ 38 ]. The modelled changes may also be less acceptable to consumers than what is assumed.…”
Section: Discussionmentioning
confidence: 99%
“…The modelled changes may also be less acceptable to consumers than what is assumed. Vieux et al examined actual dietary patterns in six European countries, including Sweden, and concluded that exclusion of entire categories of food is not necessary to achieve health and climate benefits, and a “more sustainable” diet with “moderate” amounts of animal-based products is probably realistic, as it is already adopted by nearly one in five adults [ 38 ] corresponding to the population segments innovators, early adopters and some of the early majority according to the Diffusion of Innovations theory [ 8 ]. We therefore made sure to include scenarios where animal-based products were still included to a large degree, as well as being more extensively reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The “dairy-based diet” of the cohort was somewhat healthier and had higher dietary GHGE, which corresponds to our “high dairy, low fruit juices dietary pattern”. The same was observed in another study that searched for healthy and environmentally sustainable dietary patterns in five European countries, using a multiple factor analysis, focusing on GHGE and mean adequacy ratio, mean excess ratio, and solid energy density as proxies for nutritional value of the diet [ 24 ]. They found a diet that was healthier and more sustainable, in which significantly larger quantities of plant-based products and smaller quantities of meat, soft drinks, and alcoholic beverages were consumed.…”
Section: Discussionmentioning
confidence: 80%